HUBUNGAN PARITAS DENGAN KEJADIAN ANEMIA PADA IBU HAMILDI PUSKESMAS BAAMANG I KABUPATEN KOTAWINGIN TIMUR PROVINSI KALIMANTAN TENGAH TAHUN 2019 - vina anggraini (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2022)
ABSTRAK Background : Parity is the number of live or dead birth babies (Bobak,2010). Meanwhile, according to Manuaba (2010), parity is women that has given birth a term baby. Parity can divided into primipara, multipara, and grandemultipara (Prawirohardjo, 2011). Pregnancy anemia is condition of the body with hemoglobin level <11 g% in blood at first trimester and third trimester or hemoglobin level <10,5g% at second trimester (Arionang,2015). According Irianto(2014) during pregnancy, pregnant women increased blood plasma up to 30%, 18% of blood cells, but Hb only increased 19%. As a result, the frequency of anemia in pregnancy is quite high. Purpose : Find out correlation between parity with anemia in pregnant women at Baamang I Public Health Center in 2019 Research Method : This research using retrospective method with cross sectional research design. It has done at Baamang I in 2019 with 35 pregnant women samples who had anemia using total sampling technique from secondary data. Result : Bivariat analysis result using spearman rank test from 35 respondent, found that p value is 0.306 or higher than 0.05, with correlation strrength 0.178, it can be concluded there is no significant correlation between parity with anemia in pregnant women at Baamang I public health center in 2019. From the result of this research find out that majority of pregnant women are multipara wit mild anemia 14 pregnant women (73,7%). Conclusion : In this research can be concluded there is no significant correlation between parity with anemia in pregnant women. Keywords : Pregnancy, Parity, Anemia